Let's Get Ready to Rumble: Assault in Space and Time. (June 2021) - Kurland, Justin; Hill, Josh
Building on the growing literature of the spatial examination of criminality, this study examines the stability of crime related to mass gathering events over time. Specifically, we examine the impacts of baseball games on assault patterns in the Bronx and Queens, New York, using a nonparametric permutation approach to examine the spatial distribution of point patterns at the neighborhood level over multiple seasons. Findings demonstrate that Mets and Yankees game days have significant impact on the number of assaults when compared to a sample of similar non–game days providing further support for environmental criminological theories. Implications for practitioner use of the tool as well as its use as a method for researchers who seek to compare crime event patterns across several temporal bandwidths are discussed.